The Pre-Socialization of Future Journalists: An Examination of Journalism Students Professional Views in Seven Countries - Mellado-Ruiz, C (2013)
While the role of university journalism education in the professionalization of journalists has been extensively debated, systematic and comparative studies of journalism students are still scarce. This paper reports the findings from a comparative study of journalism students in seven countries: Australia, Brazil, Chile, Mexico, Spain, Switzerland, and the United States. The data show a number of similarities, but also important differences between pre-professional cultures in journalism around the world. The findings are in line with recent conceptualizations of media systems, although some variations and particularities are observed at the country level. While students in all countries reject a loyal approach and favor a citizen-oriented role, they also do so to different extents. Brazilian and Chilean students believe in the citizen-oriented and watchdog roles, whereas their counterparts in Australia, Switzerland, and the United States favor the consumer-oriented approach to a greater extent. Mexican and Spanish students, on the other hand, while supporting the citizen-oriented role, reject the loyal role comparatively less than the rest of the countries. © 2013 Taylor & Francis.